2021
DOI: 10.3390/children8060523
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of the End-of-Life Phase in Children with Life-Limiting Diseases: Retrospective Study from a Single Center for Pediatric Palliative Care

Abstract: Background: Data on the end-of-life phase of children receiving palliative care are limited. The purpose of this study is to investigate the spectrum of symptoms of terminally ill children, adolescents, and young adults, depending on their underlying disease. Methods: Findings are based on a 4.5-year retrospective study of 89 children who received palliative care before they died, investigating the symptomatology of the last two weeks before death. Results: In this study, the most common clinical symptomatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Generally, compared with the total number of hospitalised patients, high-deficit outliers are a small number of patients that cause a substantial proportion of total inpatient stay costs [49][50][51]. Considering that specialised paediatric palliative care cases are often highly complex [52], highdeficit outliers can be expected to be more prevalent in this patient population. Sufficient reimbursement of these patients' treatment costs should thus be ensured.…”
Section: Original Articlementioning
confidence: 99%
“…Generally, compared with the total number of hospitalised patients, high-deficit outliers are a small number of patients that cause a substantial proportion of total inpatient stay costs [49][50][51]. Considering that specialised paediatric palliative care cases are often highly complex [52], highdeficit outliers can be expected to be more prevalent in this patient population. Sufficient reimbursement of these patients' treatment costs should thus be ensured.…”
Section: Original Articlementioning
confidence: 99%
“…In this regard, oncological diseases account for a smaller proportion of complex diseases [ 8 ]. One area in which PPC focuses is the management and alleviation of symptoms such as pain [ 9 ], anxiety and restlessness, [ 10 ] and sleep disturbances [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most pediatric palliative care teams provide care for children with different underlying diseases, malignant as well as non-malignant. Baumann et al looked at the symptoms of 89 terminally ill children, nearly half of whom had an oncological disease [ 4 ]. They found that oncological patients had a significantly higher symptom burden at the end of life, the intensity of which increased as underlying disease progressed, and the likelihood of experiencing pain and nausea/vomiting was significantly higher in the oncological patients.…”
mentioning
confidence: 99%